CCA-secure verifiable Mix-Net protocol - Long-hai LI; Cheng-qiang HUANG; Shang-mei XU; Shao-feng FU (Tongxin xuebao)
A CCA-secure verifiable Mix-Net protocol with provable security was proposed.The protocol was based on Wikström’s Mix-Net and improves its security by introducing an improved key generation algorithm and a new method for constructing proof of secret shuffling.Without revealing the correspondence between inputs and outputs,proposed protocol enables everyone to verify the correctness of output plaintexts through checking evidences broadcasted by each server.Thus,it satisfies public verifiability.Any sender can trace and examine the processing procedure of its ciphertext.Thus,proposed protocol satisfies sender verifiability.It is prored to be CCA-secure under the assumption of random oracle.Compared with previous mix-net schemes which are CCA-secure,proposed protocol does not require any trusted center,and incurs fewer interactions between servers which also resulting in a lower computation and communication complexity.Hence,the protocol is an ideal cryptographic tool for constructing secure electronic election protocol.